Drug-loaded hydrogel microneedles for sustainable transdermal delivery of macromolecular proteins - Chandran, Rubhan; Mohd Tohit, Eusni Rahayu; Stanslas, Johnson; Salim, Norazlinaliza; Tuan Mahmood, Tuan Mazlelaa (Bentham Science Publishers, 2025)
Introduction: Poly(methyl vinyl ether co-maleic acid) (PMVE/MA) hydrogel microneedles (HMN) are investigated for transdermal delivery of macromolecular drugs owing to their biocompatibility and super-swelling properties. However, the drug delivery efficacy reduces with increasing molecular weight due to the entrapment within the HMN matrices. Furthermore, integrating external drug reservoirs extends the drug diffusion path and reduces the efficiency of drug permeation. Methods: A direct drug loading approach in the HMN matrix was introduced in this work following a pH modification step. The effect of pH modification on the physicochemical properties of HMN was studied. Then, bovine serum albumin (BSA), a model protein, was loaded into the pH-modified HMN, and the morphological changes in HMN and protein stability were also assessed. Finally, the efficacy of BSA-loaded HMN in the transdermal delivery was evaluated ex vivo. Results: A significant increase in swelling was recorded following the pH modification of HMN (p < 0.001). The structure of pH-modified hydrogel was highly porous, and ATR-FTIR spectra indicated a shift in the carboxylic peak. The secondary structure of BSA loaded in the pH-modified HMN was also preserved. The BSA-loaded HMN mediated a sustained ex-vivo drug release with a cumulative release of 64.70% (3.88 mg) in 24 h. Conclusion: Hence, the model drug-incorporated PMVE/MA HMN system shows potential for sustainable transdermal delivery of proteins.